Les apiculteurs chinois, ces pauvres hères - Caroline GRILLOT (Sociopoétiques, 2023)
In China, beekeepers generally remain in the shadows. Most are transhumant, and their rustic lifestyle and rudimentary tasks place them at odds with contemporary social norms, between the plant and animal world and the human community, strangers among their compatriots. In the eyes of a Chinese society that values the group, their existence remains associated with the image of poor, hard-working and solitary peasants, almost marginal, despite their genuine entrepreneurial commitment. In social representations, beekeepers are either folkloric or invisible, free and therefore suspect, and potentially exploitable. Drawing on contemporary literature, documentary and journalistic production, we will sketch out the contours of this little-known profession as seen by its Chinese compatriots.